2013
DOI: 10.1371/journal.ppat.1003279
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza A Viruses Escape from Restriction by Human MxA through Adaptive Mutations in the Nucleoprotein

Abstract: The interferon-induced dynamin-like MxA GTPase restricts the replication of influenza A viruses. We identified adaptive mutations in the nucleoprotein (NP) of pandemic strains A/Brevig Mission/1/1918 (1918) and A/Hamburg/4/2009 (pH1N1) that confer MxA resistance. These resistance-associated amino acids in NP differ between the two strains but form a similar discrete surface-exposed cluster in the body domain of NP, indicating that MxA resistance evolved independently. The 1918 cluster was conserved in all desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
314
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(325 citation statements)
references
References 65 publications
10
314
0
1
Order By: Relevance
“…5). These residues are solvent exposed and therefore readily accessible for cellular factors, such as the Mx1 protein (95). We recently demonstrated that Mx1 interacts with both the NP and PB2 proteins and disturbs their interaction by a mechanism that depends on GTP binding and/or GTPase activity.…”
Section: Antiviral Activity Against Orthomyxoviridaementioning
confidence: 99%
See 1 more Smart Citation
“…5). These residues are solvent exposed and therefore readily accessible for cellular factors, such as the Mx1 protein (95). We recently demonstrated that Mx1 interacts with both the NP and PB2 proteins and disturbs their interaction by a mechanism that depends on GTP binding and/or GTPase activity.…”
Section: Antiviral Activity Against Orthomyxoviridaementioning
confidence: 99%
“…This nonhydrolyzable GTP analog pre- The residues important for Mx1 and MxA resistance are highlighted in red. Residues that contribute in only a minor way to Mx1 resistance are indicated in light red (95). Right, these important residues are also exposed on the surface of viral ribonucleoprotein (RNP) complexes (PDB file 4BBL [146]).…”
Section: Thovmentioning
confidence: 99%
“…Interestingly, these twoIAVstrainsdevelopedtheirMxAresistancephenotypeindependently of each other (19) and, therefore, introduced distinct adaptive mutations into their NP coding sequence. These findings led us to the conclusion that there are at least two mechanisms for IAV to evade restriction by MxA.…”
Section: Discussionmentioning
confidence: 99%
“…Dimeric Variants of MxA Interact with NP Independent of Other Viral Proteins-Despite the fact that, so far, experimental evidence for a physical interaction of human MxA with NP is lacking, the available data strongly suggest a functional relationship between these two proteins (18,19,33) (Fig. 5B).…”
Section: Mxa Inhibits Iav Replication At Amentioning
confidence: 99%
See 1 more Smart Citation